Correlation of hs-CRP with environmental risk factors of nephropathy in type 2 diabetes (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of the present study was to investigate the association of hs-CRP levels with environmental risk factors of diabetic nephropathy like smoking, drinking alcohol, diet, age of diabetic patient, duration of diabetes, medication of diabetes, and blood pressure medication. A hospital-based quantitative study was conducted at the Department of Clinical Biochemistry of Manipal Teaching Hospital (MTH) Pokhara, Nepal, with 89 patients suffering from type 2 diabetes. Blood samples (n=89) from the patients were collected and the serums were separated. On the other hand, data on environmental risk factors of nephropathy were collected by using standard questionnaire. In this study, serum hs-CRP level was not found to be correlated with smoking (p=0.111), alcohol consumption (p=0.722), diet (p=0.496), duration of diabetes (p=0.519), age of diabetic patient (p=0.369), medication of diabetes (p=0.734), and blood pressure medication (p=0.625). Hence, our study concludes that serum hs-CRP value in type 2 diabetic patients is insignificantly correlated with the risk factors especially smoking, drinking alcohol, diet, duration of diabetes, age of diabetic patient, medication of diabetes, and medication of blood pressure. http://dx.doi.org/10.5455/javar.2015.b80